Sonochemical Reaction of Bifunctional Molecules on Silicon (111) Hydride Surface - Serge Ismael Zida; Yue-Der Lin; Yit Lung Khung (Molecules, 2021)
While the sonochemical grafting of molecules on silicon hydride surface to form stable Si–C bond via hydrosilylation has been previously described, the susceptibility towards nucleophilic functional groups during the sonochemical reaction process remains unclear. In this work, a competitive study between a well-established thermal reaction and sonochemical reaction of nucleophilic molecules (cyclopropylamine and 3-Butyn-1-ol) was performed on p-type silicon hydride (111) surfaces. The nature of surface grafting from these reactions was examined through contact angle measurements, X-ray photoelectron spectroscopy (XPS) and atomic force microscopy (AFM). Cyclopropylamine, being a sensitive radical clock, did not experience any ring-opening events. This suggested that either the Si–H may not have undergone homolysis as reported previously under sonochemical reaction or that the interaction to the surface hydride via a lone-pair electron coordination bond was reversible during the process. On the other hand, silicon back-bond breakage and subsequent surface roughening were observed for 3-Butyn-1-ol at high-temperature grafting (≈150 °C). Interestingly, the sonochemical reaction did not produce appreciable topographical changes to surfaces at the nano scale and the further XPS analysis may suggest Si–C formation. This indicated that while a sonochemical reaction may be indifferent towards nucleophilic groups, the surface was more reactive towards unsaturated carbons. To the best of the author’s knowledge, this is the first attempt at elucidating the underlying reactivity mechanisms of nucleophilic groups and unsaturated carbon bonds during sonochemical reaction of silicon hydride surfaces.